Alluvial fan deposition along a rift depocentre border from the Neuquén Basin, Argentina - Muravchik, Martin (2014)
The interaction between hangingwall block rotation and alluvial deposition is examined from Late Triassic–Early Jurassic successions exposed along the Catán Lil half-graben border fault system in the Neuquén Basin, Argentina. Analysis of transport and depositional processes, clast composition and rock body geometry allowed the identification of three distinctive fan-shaped alluvial units. The contrasting lithologic nature of the basement (igneous-metamorphic) and syn-rift fill (volcanic and volcanic-derived) permits detailed studies of clast provenance. The origin of each alluvial system (footwall- vs. hangingwall-derived) can thus be verified. A simple method was implemented to establish the geometry of each alluvial unit by comparing the stereographic projection of its bedding to that of an idealised fan shaped body. Results show that the three alluvial systems occupied the same relative location in the rift depocentre. Unit 1 is interpreted as an alluvial fan orientated transverse to the depocentre border fault system and fed from the footwall. Non-cohesive debris flow deposition was the dominant process in this environment. Unit 2 is interpreted as a mainly hangingwall-fed alluvial fan, parallel to the depocentre border fault system and shows an upward decrease in footwall-derived clasts. Hyperconcentrated flow was the principal transport process. Unit 3 represents a fan delta, parallel to the depocentre border fault system. Its components are completely hangingwall-derived and hyperconcentrated flow deposition was the dominant process. Differences in grain-size, composition, transport directions and fan body geometry are proved to be directly linked to variations in ground tilting induced by the direction of hangingwall block rotation in an endorheic rift depocentre.